Analisis Frasa Endosentrik dalam Teks Laporan Observasi pada Buku Bahasa Indonesia Kelas X Kurikulum Merdeka - Devia Reski Novella; Hanum Sa’ada Fidaroeni; Ras Tuti Analiah; Wiwik Fitriyani; Asep Purwo Yudi Utomo; Titi Wuryani (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
This study examines phrases based on word classes in the text of the observation report on the Indonesian Language Book Class X Independent Curriculum. This study aims to determine the class of endocentric phrases consisting of nominal phrases, verbal, and adjectival and their structure. This method used a qualitative method with an inductive approach, the source of the data is found in the Indonesian Class X Book of Independent Curriculum. Data collection techniques by reading, recording texts, analyzing data, and arranging phrases according to their classification. The data analysis technique uses descriptive techniques. The study resulted in 33 nominal phrases, 13 verbal phrases, and 6 injective phrases. With 10 structures of Subordinative Nominal Phrases (N+N), Subordinate Nominal Phrases (N+A), Subordinate Nominal Phrases (Num+N), Subordinative Injective Phrases (Adv+A), Subordinate Injective Phrases (A+A), Subordinate Injective Phrases (A+N), Subordinate Injective Phrases (V+A), Subordinate Verbal Phrases (V+A), Coordinate Nominal Phrases, and Subordinate Verbal Phrases Adv+V. The benefit of this study is that it improves understanding of phrases, specifically the endocentric phrase.